Scientific Literacy Level of Biology Education Students, University of Mataram, Indonesia - G Hadiprayitno, A Ramdani, K Karnan, I P Artayasa, A Sukri, J Susilo (International Journal of Advanced Science and Technology, 2020)
This study aims to determine: 1) scientific literacy level of Biology Education students, 2) differences in science literacy level of students based on semester, and 3) correlation between scientific literacy level and student learning experience. This research was a descriptive study with a quantitative approach performed on 179 Biology Education students, Faculty of Education, University of Mataram, Indonesia. The results showed that: 1) scientific literacy level of students was in a low category with a mean score of 57.00; 2) scientific literacy level of students was different between semesters with the highest scores obtained by students at VII semester with a mean score of 62.33; 3) scientific literacy level of students was positively correlated with the student learning experience as evidenced by the increase in student average scores from semester III to semester VII, and 4) scientific literacy level of students was high for conceptual or process dimension, and very low for the context dimension.Keywords: biology teacher candidates, scientific literacy, biology education students.